357 Demographics and Characteristics of Hydrocephalus in Adults: The First 500 Subjects of the Adult Hydrocephalus Clinical Research Network Registry. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Williams, Michael A; Luciano, Mark G; Nagel, Sean J; Relkin, Norman; Zwimpfer, Thomas J; Katzen, Heather; Holubkov, Richard; Hamilton, Mark G
Abstract: INTRODUCTION: The characteristics of the adult population with hydrocephalus are not well described. The Adult Hydrocephalus Clinical Research Network (AHCRN), founded in 2014, initially comprised University of Calgary, University of British Columbia, Cleveland Clinic, Weill Cornell Medical College, Sinai Hospital of Baltimore, University of Washington, and University of Utah (Data Coordinating Center). METHODS: Adults ≥18 yr were nonconsecutively enrolled in a registry. Data include symptoms, examination, neuropsychology screening, comorbidities, imaging, treatment, complications, and outcomes. Four categories were defined: transition (treated before age 18), congenital (congenital pattern, not treated before age 18), acquired (secondary to known risk factors, treated or untreated), and possible idiopathic normal pressure hydrocephalus (≥age 65 yr, not previously treated). We report the first 519 subjects (2015-2017). RESULTS: Demographics—sex: female 42.0%; age at enrollment: 59.8 ± 19.2 yr (range: 18.1-90.7); race: white 90.6%, Asian 5.0%, black 1.7%, missing/other 2.7% category; transition: n = 86 (16.6%); congenital: n = 132 (25.4%); acquired: n = 88 (17.0%); possible INPH: n = 213 (41.0%). Category variation among 6 centers—transition: 0 to 43%; congenital: 0 to 42.2%; acquired: 8.7 to 31.9%; possible INPH: 19.0 to 85.7%. Treatment at time of enrollment—all subjects: 36.8% (shunt 26.8%, ETV 10.0%); transition: 100% (shunt 95.3%, ETV 14.0%); congenital: 43.2% (shunt 22.0%, ETV 21.2%); acquired: 39.2% (shunt 27.5%, ETV 11.8%); possible INPH: 0% (by definition) Top etiologies—transition: myelomeningocele 33.7%, aqueductal stenosis 15.1%, IVH of prematurity 9.3%; congenital: communicating 41.7%, aqueductal stenosis 50.0%, aqueductal pattern 15.2%; acquired: brain tumor 28.4%, intraventricular adhesion/web/colloid cyst 13.7%, nontraumatic SAH 11.8%, TBI 9.8% Lawton ADL Score (lower = better); transition: 3.1 ± 4.0; congenital: 1.5 ± 2.7; acquired: 4.1 ± 5.9; INPH: 5.5 ± 5.2. CONCLUSION: The population in the AHCRN registry is diverse. A combined 42% have childhood onset, whether treated or untreated by age 18, and only 41% are possible INPH. The degree of impairment (Lawton ADL) is least in the Congenital group and worst in possible INPH. The proportion of hydrocephalus categories varied widely among centers. More research on the lifespan needs and outcomes for adult hydrocephalus is needed.